Logistics and distribution innovation in China. Issue 3 (31 December 0018) - Amling, Alan; Daugherty, Patricia J.
Abstract : Purpose: The purpose of this paper is to explore how two mega-trends, e-commerce and urbanization, have the potential to reshape logistics practices around the world. Primary focus is on how Chinese business practices and logistics innovations are increasingly relevant to the USA and other western countries. Design/methodology/approach: Experience-based thought piece focusing on specific Chinese logistics innovations centering on speed, adaptability and new business models. Findings: The Chinese economy has played a key role in providing support and enabling logistics innovations in China. Key enablers include the ubiquitous connectivity and applications availability, the dynamic low-cost labor environment and government support for the Chinese logistics industry. Research limitations/implications: This study suggests new areas for research. Practical implications: This study provides insights into the potential value associated with adopting innovative Chinese logistics practices. Social implications: This study provides suggested areas of attention to help focus on logistics operations on key societal trends. Originality/value: Our paper provides insights into the potential value associated with adopting innovative Chinese logistics practices. We believe this represents a significant contribution as little coverage of the topics have been noted to date in leading logistics/supply chain journals.